2009
DOI: 10.1614/wt-08-126.1
|View full text |Cite
|
Sign up to set email alerts
|

Olive Processing Waste as a Method of Weed Control for Okra, Faba Bean, and Onion

Abstract: Field experiments were carried out during two growing seasons at Adnan Menderes University, Faculty of Agriculture, in Aydın-Turkey to evaluate the weed control efficacy of olive processing waste (OPW) in okra, faba bean, and onion. OPW was incorporated into the soil prior to seeding at 10, 20, 30, and 40 tons (t)/ha. Non-treated plots and plots treated with trifluralin in okra and pendimethalin in faba bean and onion were used for comparison. OPW suppressed common purslane, redroot pigweed, and junglerice in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Ghosheh et al (1999) demonstrated that OPW could be used for control of an important parasitic weed species, Orobanche spp., in pot experiments. In a recent study Boz et al (2009) showed that OPW suppresses effectively some important winter and summer weeds, including A. retroflexus, and that OPW showed no harmful effect on V. faba, so that the results recorded here confirm those in the other study.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Ghosheh et al (1999) demonstrated that OPW could be used for control of an important parasitic weed species, Orobanche spp., in pot experiments. In a recent study Boz et al (2009) showed that OPW suppresses effectively some important winter and summer weeds, including A. retroflexus, and that OPW showed no harmful effect on V. faba, so that the results recorded here confirm those in the other study.…”
Section: Resultssupporting
confidence: 89%
“…Similar recommendations were made also following some other studies. In our earlier work it was observed that OPW reduced the number of P. oleracea significantly Boz et al 2003Boz et al , 2009. In another study, water extracts of olive mill waste reduced the germination of A. retroflexus by more than 90% and the germination of S. nigrum by 48-90%, whereas the germination of C. album and S. halepense was not decreased (Cayuela et al 2008).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…It was further suggested that OMW could be considered as a useful, low-cost soil amendment and fertilizer (Chartzoulakis, Psarras, Moutsopoulou, & Stefanoudaki, 2010;Gargouri et al, 2013;Hanifi & El Hadrami, 2008;Laor et al, 2011;Tomati, Galli, Fiorelli, & Pasetti, 1996), although OMW application caused a drastic reduction in soil mineral-N indicating net N immobilization (Karpouzas et al, 2010). OMW showed its potential to serve as environmental friendly bio-herbicide (Boz, Dogan, & Albay, 2003;Boz, Ogüt, Kir, & Dogan, 2009), and finally, in regions having low soil organic matter (SOM) content and consequently low soil fertility, OMW can serve as a readily available organic matter (OM) source.…”
mentioning
confidence: 99%